Purification and characterization of an alpha-galactosidase from Aspergillus fumigatus - Sebastião Tavares de Rezende; Valéria Monteze Guimarães; Marília de Castro Rodrigues; Carlos Roberto Felix (Brazilian Archives of Biology and Technology, 2005)
Aspergillus fumigatus secreted invertase (beta-fructofuranosidase) and alpha-galactosidase enzymatic activities able to hydrolyzing raffinose oligosaccharides (RO). alpha-Galactosidase was induced by galactose, melibiose and raffinose, but galactose was the most efficient inducer. It was purified by gel filtration and two ion exchange chromatographies and showed Mw of 54.7 kDa. The purified enzyme showed maximal activity against p-nitrophenyl-alpha-D-galactopyranoside (pNPGal) at pH 4.5-5.5 and 55 °C, and retained about 80% of the original activity after incubation for 90 minutes at 50ºC. The KM for pNPGal was 0.3 mM. Melibiose was hydrolyzed by the enzyme but raffinose was very poor substrate. O fungo termofílico Aspergillus fumigatus secreta as enzimas invertase (beta-frutofuranosidase) e alfa-galactosidase (alfa-D-galactosídeo galactohi-drolase) que estão envolvidas na hidrólise completa dos oligossacarídeos de rafinose. A enzima alfa-galactosidase foi produzida em meio de cultura do fungo Aspergillus fumigatus crescido por 36 h a 42 °C em meio mineral mínimo contendo os açúcares galactose, ou melibiose, ou rafinose como fontes de carbono. A enzima foi purificada por filtração em gel, seguida por duas cromatografias de troca iônica. A massa molecular da alfa-galactosidase determinada por SDS-PAGE foi de 54,7 kDa. A atividade máxima da enzima purificada, utilizando o substrato ro-nitrofenil-alfa-D-galactopiranosídeo (roNPGal) foi na faixa de pH entre 4,5 e 5,5 e a 55 °C. A enzima manteve aproximadamente 80% de sua atividade original mesmo após pré-incubação por 90 minutos a 50 °C. O valor de KM para o substrato roNPGal foi 0,3 mM. A enzima foi capaz de hidrolisar melibiose, mas sua atividade foi muito reduzida na presença do substrato rafinose.